Development of Intelligent Façade Based on Outdoor Environment and Indoor Thermal Comfort. (2015) - Ahmed, Mostafa M.S.; Abel-Rahman, Ali K.; Ali, Ahmed Hamza H.
Abstract: In the last decades, the development of innovative solutions is considered as a prominent issue for achieving sustainability within the built environment. Facades are crucial to energy consumption and comfort within buildings. Incorporating intelligence in their design is an effective way to achieve low energy consumption buildings. The ability of specific facade systems to work reliably and effectively is one of the challenges towards sustainability. This study presents the state of art for intelligent facades at different outdoor environment in different climates. In addition the indoor environmental parameters such as thermal comfort, indoor air quality and visual comfort are outlined. The study concluded that intelligent facades in buildings and indoor thermal comfort require more development targeting low energy buildings and thermal comfort.